1981
DOI: 10.1128/iai.34.2.362-367.1981
|View full text |Cite
|
Sign up to set email alerts
|

Mode of Action of Staphylococcal Leukocidin: Relationship between Binding of 125 I-Labeled S and F Components of Leukocidin to Rabbit Polymorphonuclear Leukocytes and Leukocidin Activity

Abstract: The binding of "2'I-labeled S component to rabbit polymorphonuclear leukocytes was found to be concentration dependent and saturable at 37°C. Scatchard analysis of the binding curve gave a straight line, indicating that S component binds to a single population of sites. The dissociation constant, KD, derived from the Scatchard plot was 5.57 x 10-9 M, and the number of binding sites per leukocyte was calculated to be approximately 5,300. Unlabeled S component (10-8 M) or subunit B of cholera toxin (10-7 M) read… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

1983
1983
2001
2001

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…Cytotoxic action of leukocidin to rabbit polymorphonuclear leukocytes (8)(9)(10)(11)(12) and HL-60 cells (3)(4)(5)(6) has been reported. The mode of action was thought to be as follows: After binding of leukocidin to specific receptors, the activation of membrane-associated enzymes just like phospholipase A2 and phospholipase C occurred, resulting in membrane perturbation including changes in ion permeability and leukocytolysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytotoxic action of leukocidin to rabbit polymorphonuclear leukocytes (8)(9)(10)(11)(12) and HL-60 cells (3)(4)(5)(6) has been reported. The mode of action was thought to be as follows: After binding of leukocidin to specific receptors, the activation of membrane-associated enzymes just like phospholipase A2 and phospholipase C occurred, resulting in membrane perturbation including changes in ion permeability and leukocytolysis.…”
Section: Discussionmentioning
confidence: 99%
“…phocytes and other cells (2,9,11,14). S and F components specifically bind to ganglioside GMl and phosphatidylcholine, respectively (9,10). In the previous paper, it was reported that the specific binding of leukocidin to rabbit polymorphonuclear leukocytes induced activation of phospholipase A2 (11) and phospholipase C in leukocyte membrane (17) and it was suggested that those activities are responsible for the primary action of leukocidin leading to calcium and potassium ion permeability changes in membrane (11).…”
mentioning
confidence: 99%
“…Preparations of the labeled S and F components had specific activities of 9 x 105 to 2 x 106 cpm/ILg of protein. Binding of 125I-labeled leukocidin to polymorphonuclear leukocytes was assayed as described previously (12).…”
Section: Chemicalsmentioning
confidence: 99%
“…Staphylococcal leukocidin consists of two protein components (S and F) that act synergistically to induce cytotoxic changes in human and rabbit polymorphonuclear leukocytes. Previously (7,10,12,14) we reported that the S and F components of leukocidin were preferentially bound and inactivated by GM1 ganglioside and phosphatidylcholine, respectively, in rabbit polymorphonuclear leukocyte membranes. The specific binding of the S component to GM1 ganglioside induces activation of cell membrane-associated phospholipase A2, resulting in the release of prostaglandins and leukotrienes from the cells and then in enhancement of chemotaxis of polymorphonuclear leukocytes (11,13).…”
mentioning
confidence: 91%
“…The leukocidin of Pseudomonas aeruginosa was firstly described in 1976 by Scharmann (18) and showed a striking resemblance to the biological activity ofstaphylococcal leukocidin (13)(14)(15)(16)26) inflicting a series of morphological changes on rabbit leukocytes but not on rabbit erythrocytes. However, the differences of the mode of toxic actions of these leukocidins were enormous.…”
mentioning
confidence: 99%